Pengaruh Keaktifan Mahasiswa Dalam Kegiatan Organisasi Dan Magang Administrasi Perkantoran Terhadap Communication Skills Mahasiswa - Ria Cahyaningrum; Wiedy Murtini; Anton Subarno (Politeknik Kampar, 2023)
The purpose of this study is to find out: (1) the effect of Student Activeness in Organization Activities on student communication skills, (2) the effect of Office Administration Internships on student communication skills, (3) the effect of Student Activities in Organization Activities and Office Administration Internships on student communication skills of student of Office Administration Education Sebelas Maret University. The research method used descriptive correlational with a quantitative associative approach. Data collection technique carried out by using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques with the help of the SPSS 26 program. The results of this study are: (1) there is a positive and significant effect of student activeness in organizational activities on student communication skills (tcount(2,64) > ttable(2,01)); (2) there ias a positive and significant effect of office administration internships on student communication skills (tcount(3,59) > ttable(2,01)); (3) there is a positive and significant effect of student activeness in organizational activities and office administration internships on student communication skills (Fcount(12,72) > Ftable(3,22)). The regression equation obtained is Y = 7,16 + 0,49 X? + 0,40 X?